Boilers a Practical reference - Rayaprolu K. Kumar (New York, Taylor & Francis, 2012)
A unique encyclopedic guide to all aspects of boiler design and technology, entries address key foundational concepts and cover all types of boilers found in process industries and power plants. The book also addresses all major auxiliary equipment, including air pollution control technologies. Key subject areas include fundamentals such as heat transfer, fluid flow, and metallurgy; engineering, including boiler components, pressure parts, and boiler instrumentation; essential auxiliaries, including mounting and fittings, pumps, and valves; and various types of boilers. The book also covers the latest clean and green technologies.